Study protocol for the assessment of nurses internal contamination by antineoplastic drugs in hospital centres: a cross-sectional multicentre descriptive study. Issue 11 (10th November 2019) - Villa, Antoine; Molimard, Mathieu; Bignon, Emmanuelle; Martinez, Béatrice; Rouyer, Magali; Mathoulin-Pelissier, Simone; Baldi, Isabelle; Verdun-Esquer, Catherine; Canal-Raffin, Mireille
Abstract : Introduction: Antineoplastic drugs (AD) are potentially carcinogenic and/or reprotoxic molecules. Healthcare professionals are increasingly exposed to these drugs and can be potentially contaminated by them. Internal contamination of professionals is a key concern for occupational physicians in the assessment and management of occupational risks in healthcare settings. Objectives of this study are to report AD internal contamination rate in nursing staff and to identify factors associated with internal contamination. Methods and analysis: This trial will be conducted in two French hospital centres: University Hospital of Bordeaux and IUCT-Oncopole of Toulouse. The target population is nurses practicing in one of the fifteen selected care departments where at least one of the five studied AD is handled (5-fluorouracil, cyclophosphamide, doxorubicin, ifosfamide, methotrexate). The trial will be conducted with the following steps: (1) development of analytical methods to quantify AD urine biomarkers, (2) study of the workplace and organization around AD in each care department (transport and handling, professional practices, personal and collective protection equipments available) (3) development of a self-questionnaire detailing professional activities during the day of inclusion, (4) nurses inclusion (urine samples and self-questionnaire collection), (5) urine assays, (6) data analysis. Ethics and dissemination: The study protocol has been approved by the French Advisory Committee on the Treatment of Information in Health Research (CCTIRS) and by the French Data Protection Authority (CNIL). Following the opinion of the Regional Committee for the Protection of Persons, this study is outside the scope of the provisions governing biomedical research and routine care (n°2014/87). The results will be submitted to peer-reviewed journals and reported at suitable national and international meetings. Trial registration number: NCT03137641 .